Transcription start site‐level expression of thyroid transcription factor 1 isoforms in lung adenocarcinoma and its clinicopathological significance - Kei Sano; Takuo Hayashi; Yoshiyuki Suehara; Masaki Hosoya; Kazuya Takamochi; Shinji Kohsaka; Satsuki Kishikawa; Monami Kishi; Satomi Saito; Fumiyuki Takahashi; Kazuo Kaneko; Kenji Suzuki; et al. (Wiley, 2021)
Abstract There are multiple transcription start sites (TSSs) in agreement with multiple transcript variants encoding different isoforms of NKX2‐1/TTF‐1 (thyroid transcription factor 1); however, the clinicopathological significance of each transcript isoform of NKX2‐1/TTF‐1 in lung adenocarcinoma (LAD) is unknown. Herein, TSS‐level expression of NKX2‐1/TTF‐1 isoforms was evaluated in 71 LADs using bioinformatic analysis of cap analysis of gene expression (CAGE)‐sequencing data, which provides genome‐wide expression levels of the 5'‐untranslated regions and the TSSs of different isoforms. Results of CAGE were further validated in 664 LADs using in situ hybridisation. Fourteen of 17 TSSs in NKX2‐1/TTF‐1 (80% of known TSSs in FANTOM5, an atlas of mammalian promoters) were identified in LADs, including TSSs 1-13 and 15; four isoforms of NKX2‐1/TTF‐1 transcripts (NKX2‐1_001, NKX2‐1_002, NKX2‐1_004, and NKX2‐1_005) were expressed in LADs, although NKX2‐1_005 did not contain a homeodomain. Among those, six TSSs regulated NKX2‐1_004 and NKX2‐1_005, both of which contain exon 1. LADs with low expression of isoforms from TSS region 11 regulating exon 1 were significantly associated with poor prognosis in the CAGE data set. In the validation set, 62 tumours (9.3%) showed no expression of NKX2‐1/TTF‐1 exon 1; such tumours were significantly associated with older age, EGFR wild‐type tumours, and poor prognosis. In contrast, 94 tumours, including 22 of 30 pulmonary invasive mucinous adenocarcinomas (IMAs) exhibited exon 1 expression without immunohistochemical TTF‐1 protein expression. Furthermore, IMAs commonly exhibited higher exon 1 expression relative to that of exon 4/5, which contained a homeodomain in comparison with EGFR‐mutated LADs. These transcriptome and clinicopathological results reveal that LAD use at least 80% of NKX2‐1 TSSs and expression of the NKX2‐1/TTF‐1 transcript isoform without exon 1 (NKX2‐1_004 and NKX2‐1_005) defines a distinct subset of LAD characterised by aggressive behaviour in elder patients. Moreover, usage of alternative TSSs regions regulating NKX2‐1_005 may occur in subsets of LADs.